Programas infantiles televisivos y su influencia en el proceso de enseñanza-aprendizaje - Meza Ramos, Génesis Mariuxi (2018)
Children's programs and their content of violence, known in some television channels, mark on people and children a certain influence in the teaching-learning process. This research work has a socio-educational orientation since it takes into account the situation where the child develops, as well as the relationship that exists with parents at home, in addition to the relationship with the school and its teachers. A series of research tools was used, such as the parents' survey, the teacher's interview, taking into account the theoretical framework, the objectives, the variables and, in this way, look for possible solutions to deal with these issues with responsibility. With this bibliographical, documentary and field research according to the variables, it is sought to conclude that the children's programs that transmit most of them, are of violent content, affect the emotion of the boys and girls of the educational center and cause low performance in the teaching-learning process